Case report: Novel NUS1 variant in a Chinese patient with tremors and intellectual disability - Li, Ruolin; Yang, Jiayi; Ma, Jinfeng; Zhang, Aimei; Li, Hongfang (Frontiers in Genetics, 2024)
Introduction: Nuclear undecaprenyl pyrophosphate synthase 1 (NUS1) gene variants are associated with a range of phenotypes, including epilepsy, intellectual disability, cerebellar ataxia, Parkinson’s disease, dystonia, and congenital disorders of glycosylation. Additionally, cases describing genotypes and clinical features are rare. Case Presentation: Herein, we report the case of a 23-year-old Chinese female patient who presented with tremors, intellectual disability, and epilepsy. A history of carbon monoxide exposure, brain trauma, or encephalitis was not present in this case. Trio whole-exome sequencing analysis revealed a de novo pathogenic variant of c.750del in exon 4, leading to p.Leu251* amino acid substitution. Genetic analysis failed to identify the identical mutations in the remaining family members who underwent screening. The patient was diagnosed with a rare congenital disease, “congenital glycosylation disorder, type 1aa, autosomal dominant, type 55, with seizures (MRD-55).” Conclusion: We provide further evidence for the role of variants in NUS1 in the development of tremors, epilepsy, and intellectual disabilities. These findings expand our understanding of the clinical phenotypes of NUS1 variants.